1995
DOI: 10.1093/ageing/24.6.490
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Leg Ulcer Recurrence: A Randomized Trial of Two Types of Compression Stocking

Abstract: Patients with recently healed leg ulceration were entered into a study of leg ulcer recurrence. In all, 188 patients [69% women, mean age = 72 (SD = 12) years] were entered into the study, of whom 166 were considered suitable for ready-made stockings and were randomized to one of two class II below-knee compression stockings and followed for at least 18 months. The remaining patients required either made-to-measure stockings (5) or could not tolerate stockings owing to friable skin and were treated by other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 0 publications
5
99
0
2
Order By: Relevance
“…Compliance data reported from this trial as summarized in Nelson and Bell-Syer demonstrated that inability to tolerate compression therapy was significantly associated with recurrent ulceration (RR, 2.58; 95% CI, 1.33-5.01; P ¼ .010), although these patients were not included in randomization. 289,291 These RCT data are congruent with 15 years of observational data demonstrating that lack of compliance with compression therapy was significantly associated with ulcer recurrence (16% recurrence with compliance, 100% without; P < .0001). 292 Two studies to date have evaluated the use of moderate (UK class II, 18-24 mm Hg at the ankle) to high (UK class III, 25-35 mm Hg) compression and compliance with these stockings on prevention of ulcer recurrence, with differing results.…”
Section: Compressionsupporting
confidence: 69%
“…Compliance data reported from this trial as summarized in Nelson and Bell-Syer demonstrated that inability to tolerate compression therapy was significantly associated with recurrent ulceration (RR, 2.58; 95% CI, 1.33-5.01; P ¼ .010), although these patients were not included in randomization. 289,291 These RCT data are congruent with 15 years of observational data demonstrating that lack of compliance with compression therapy was significantly associated with ulcer recurrence (16% recurrence with compliance, 100% without; P < .0001). 292 Two studies to date have evaluated the use of moderate (UK class II, 18-24 mm Hg at the ankle) to high (UK class III, 25-35 mm Hg) compression and compliance with these stockings on prevention of ulcer recurrence, with differing results.…”
Section: Compressionsupporting
confidence: 69%
“…77 Made to measure hosiery is available and should be offered when fitting is otherwise difficult. Devices are available which may be useful for patients who find the application of stockings difficult.…”
Section: A Below-knee Graduated Compression Hosiery Is Recommended Tomentioning
confidence: 99%
“…5,6 When treated with the current standard of care, about 30% of VLUs remain unhealed at 6 months. 7 Even if healed, approximately 26% to 34% of VLUs recur within 1 year [8][9][10][11] and 56% within 4 years. 12 Given these results, there is a compelling need for new therapies that offer improved efficacy for the management of VLUs.…”
mentioning
confidence: 99%